A Benzene Ring‐Linked Dimethylamino and Borate Ester‐Based Molecule and Organic Crystal: Efficient Dual Room‐Temperature Phosphorescence with Responsive Property. Issue 17 (14th June 2022) - Xie, Ning; Wang, Jiaxuan; Huang, Tingting; Zhao, Liupeng; Sun, Peng; Lu, Geyu; Wang, Yue; Li, Chenglong
Abstract: Pure organic crystal of N, N ‐di‐methyl‐4‐(4, 4, 5, 5‐tetramethyl‐1, 3, 2‐dioxaborolan‐2‐yl)aniline (DMAB) exhibits efficient room‐temperature phosphorescence (RTP) with an emission maximum at 387 nm and a high phosphorescence efficiency of 35.2%. Significantly, DMAB shows an exceptional photo‐induced ultra‐long RTP (URTP) at 539 nm, which displays an afterglow time of 14 s in air. The two phosphorescent bands are attributed to the monomeric and aggregated RTP of DMAB, respectively. Continuous UV irradiation for ≈1 min can dramatically improve the lifetimes for both of the monomeric and aggregated phosphorescent emissions. The photo‐induced URTP can be spontaneously switched off after standing the crystal in air for 50 min, and this cyclic process has been repeated several times. The molecular packing based on multiple intermolecular noncovalent interactions is adopted in DMAB crystal, which is beneficial to RTP. Upon UV irradiation, the consumption of oxygen in the crystal matrix accounts for the distinctive photo‐induced URTP. Taking advantage of the unique photo/oxygen‐sensitive properties, DMAB crystals have been successfully utilized in oxygen sensing and anticounterfeiting. Abstract : An efficient dual room‐temperature phosphorescence (RTP) material based on a pure organic crystal with a phosphorescence efficiency of 35.2% and an afterglow duration of up to 14 s under ambient conditions is developed. The phosphorescence in the long‐wavelength region possesses photo/oxygen sensitivities and has been successfully used for anticounterfeiting and oxygen sensing.